Sistem Pakar Mendiagnosa Gangguan Koneksi Internet Berbasis Web Menggunakan Algoritma Rete - Hasanah, Lailatun; Buulolo, Efori (Building of Informatics, Technology and Science (BITS), 2021)
Expert System to Diagnose Internet Connection Disorders is a series of systems that utilize digital technology to do special analysis. At PT.Telkom the Sumbagut Infratel Division already has its own website, but in providing expert system information about connection disruptions is still via the telephone, therefore a web-based expert system is designed, to facilitate the community in finding solutions to internet connection disruption. With the creation of this expert system, it is expected to provide solutions to current problems. In other words, this expert system can be said as a digital technician. The expert system to diagnose internet connection problems has been designed and implemented using the Visual Basic 2008 program and Microsoft Access as the database while the algorithm used is the Rete algorithm.This application is only admin that can process data input, edit data, and delete data. While the user can only consult and find information about internet connection disruption and the solution, with the program design that the authors make this hopefully can be used by all parties.